Improving Information Support of Research, Technical, and Innovation Development of Khmelnytskyi Oblast Economy Through Creation of Corporate Information and Analytical System - Kravchuk, V.V.; Grynchuk, V.M.; Grynchuk О.V. (Science and Innovation, 2024)
The paper deals with a method for building up the data array of corporate informational and analytical system of Khmelnytskyi Oblast. This method is aimed at organizing information exchange between different information systems of member enterprises and institutions of the corporate information-analytical system.